USE OF INFORMATION TECHNOLOGY IN THE SOUND “S” CORRECTION PROCESS FOR 5–6–YEAR–OLD CHILDREN WITH PHONETIC DISORDERS - Kalmikova, Jelena; Vindece, Aija (Education Reform: Education Content Research and Implementation Problems, 2021)
Today, the pre–school education system is undergoing major changes aimed at improving the quality of education. New approaches, methods, and programmes are being developed. There is an increased need to introduce innovative technologies that are designed to gain new knowledge, accelerate the process of obtaining knowledge, improve the quality of education, and increase the motivation of children. The development of speech, which includes the ability to clearly pronounce sounds and distinguish them, to control the articulation apparatus, to correctly form a sentence, is one of the most urgent tasks that speech therapists at pre–school institutions should solve.